2013
DOI: 10.1002/hep.26018
|View full text |Cite
|
Sign up to set email alerts
|

Anticholestatic effects of bezafibrate in patients with primary biliary cirrhosis treated with ursodeoxycholic acid

Abstract: Bezafibrate is a widely used hypolipidemic agent and is known as a ligand of the peroxisome proliferator-activated receptors (PPARs). Recently this agent has come to be recognized as a potential anticholestatic medicine for the treatment of primary biliary cirrhosis (PBC) that does not respond sufficiently to ursodeoxycholic acid (UDCA) monotherapy. The aim of this study was to explore the anticholestatic mechanisms of bezafibrate by analyzing serum lipid biomarkers in PBC patients and by cell-based enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
132
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 55 publications
2
132
1
Order By: Relevance
“…For example, Hazzan et al and Lens et al demonstrated that the addition of bezafibrate to UDCA significantly and safely improves the biochemical profiles of European patients with PBC [33,34] . The proposed mechanism of action of fibric acid derivatives in the setting of PBC involves the regulation of cell proliferation and the expression of various lipids and proteins via the activation of PPAR-α [8,10] . Through PPAR-α activation, fibrates inhibit NF-κβ activation, resulting in decreased expression levels of IL-1 and IL-6, thereby potentially reducing the inflammatory and immune responses [9,10] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Hazzan et al and Lens et al demonstrated that the addition of bezafibrate to UDCA significantly and safely improves the biochemical profiles of European patients with PBC [33,34] . The proposed mechanism of action of fibric acid derivatives in the setting of PBC involves the regulation of cell proliferation and the expression of various lipids and proteins via the activation of PPAR-α [8,10] . Through PPAR-α activation, fibrates inhibit NF-κβ activation, resulting in decreased expression levels of IL-1 and IL-6, thereby potentially reducing the inflammatory and immune responses [9,10] .…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism of action of fibric acid derivatives in the setting of PBC involves the regulation of cell proliferation and the expression of various lipids and proteins via the activation of PPAR-α [8,10] . Through PPAR-α activation, fibrates inhibit NF-κβ activation, resulting in decreased expression levels of IL-1 and IL-6, thereby potentially reducing the inflammatory and immune responses [9,10] . In addition to regulating proteins and lipids, the benefits of fibrates in cases of PBC may result from cross-talk between PPAR-α and the bile acid-activated nuclear receptor farnesoid-X-receptor (FXR) [35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PPARa decreased bile acid synthesis (CYP7A1) and induced bile acid detoxification (SULT2A1, UGT2B4, UGT1A3) in animal models (Patel et al, 2000;Jung et al, 2002;Barbier et al, 2003;Fang et al, 2005). The PPAR agonist bezafibrate showed beneficial effects in PBC patients in pilot trials, although these results need to be confirmed by larger randomized-controlled clinical trials (Honda et al, 2013).…”
Section: Canalicular Abc Transporters and Their Regulatory Nrs As Drumentioning
confidence: 95%
“…Fibrates are agonists of the nuclear receptor PPAR-alpha, with antiinflammatory and choleretic properties. Several small studies have shown significant improvement in liver biochemistries and serum IgM in patients with PBC and incomplete response to UDCA who are treated with fibrates (161)(162)(163)(164)(165)(166)(167)(168)(169)(170) . One meta-analysis of 6 randomized studies including 151 Japanese patients, concluded there was not enough evidence to support or refute an effect of bezafibrate on the morbi-mortality of patients with PBC (171) .…”
Section: Rotterdammentioning
confidence: 99%